Four new troglophilous species of the genus Pholcus Walckenaer (Araneae, Pholcidae) from Guizhou Province, China - Chen, Hui-Ming; Zhang, Feng; Zhu, Ming-Sheng (Zootaxa, 2011)
Four new troglophilous Pholcus spiders from Guizhou Province, China, are diagnosed, described and illustrated under the names: Pholcus anlong sp. nov., P. ceheng sp. nov., P. xingren sp. nov. and P.xingyi sp. nov. This is the first report on cave-dwelling Pholcus species from Guizhou Province, China.